2021
DOI: 10.1016/j.ophtha.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The Bidirectional Relationship between Vision and Cognition

Abstract: Topic: Visual impairment (VI) and cognitive impairment (CIM) are prevalent age-related conditions that impose substantial burden on the society. Findings on the hypothesized bidirectional association of VI and CIM remains equivocal. Hence, we conducted a systematic review and meta-analysis to examine this bidirectional relationship.Clinical Relevance: Sixty percent risk of CIM has not been well elucidated in the literature. A bidirectional relationship between VI and CIM may support the development of strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 88 publications
(114 reference statements)
1
61
1
Order By: Relevance
“…25,[50][51][52] For example, Hong et al 51 performed a prospective, population-based study of 3,654 participants of the Blue Mountains Eye Study in Australia and reported that VI was not associated with a ≥ 3 point decline in MMSE-Blind scores over 5 years (OR 0.84; 95% CI 0.40-1.79) or 10 years (OR = 1.09; 95% CI 0.52-2.30). This is in contrast to 4 longitudinal studies and one meta-analysis that have found a relationship between VI and cognitive function [12][13][14]53,54 and 1 study that found a relationship between visual acuity, used as a continuous variable, and cognitive decline. 55 Furthermore, several studies have found a relationship between VI and dementia or cognitive impairment [56][57][58][59][60] although not all.…”
Section: Discussioncontrasting
confidence: 60%
“…25,[50][51][52] For example, Hong et al 51 performed a prospective, population-based study of 3,654 participants of the Blue Mountains Eye Study in Australia and reported that VI was not associated with a ≥ 3 point decline in MMSE-Blind scores over 5 years (OR 0.84; 95% CI 0.40-1.79) or 10 years (OR = 1.09; 95% CI 0.52-2.30). This is in contrast to 4 longitudinal studies and one meta-analysis that have found a relationship between VI and cognitive function [12][13][14]53,54 and 1 study that found a relationship between visual acuity, used as a continuous variable, and cognitive decline. 55 Furthermore, several studies have found a relationship between VI and dementia or cognitive impairment [56][57][58][59][60] although not all.…”
Section: Discussioncontrasting
confidence: 60%
“… 31 The finding of a concurrence of vision impairment and cognitive impairment concurs also with the results of precent meta-analyses. 33 34 …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, VEP have been used to observe the transmission of light signals to a subcortical nucleus and the visual cortex and this illustrates the extent of the visual pathway [ 37 ]. Damage to somewhere of visual pathway can lead to visual impairment, which affects the normal lives and leads to negative emotions [ 38 ], cognitive impairment [ 39 ] and poor motor perception [ 40 ]. Previous studies had demonstrated that there were retinal ganglion cells loss or apoptosis [ 41 , 42 ] and retinal nerve fiber layer thinner or loss in DR patients [ 43 ], but there were less than half of DR patients had optic neuropathy [ 5 ] and this neurodegeneration was an early event in the pathogenesis of DR [ 44 ].…”
Section: Discussionmentioning
confidence: 99%